ANALISIS SEMANTIK PADA PUISI "CINTAKU JAUH DI PULAU" KARYA CHAIRIL ANWAR - Desih Pratiwi; Dewi Purnamasari; Fauziah Nurul Fatimah; Latifah Latifah (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
A poem is a kind of literature that is interested in all society. Not only for reading it, but some of them are interested to produce a poem. In the language thing, poem tends to free,  unbounded with the particular rules. The use of analogical terms makes us difficult to comprehend the hidden meaning inside it. This research is done to describe the meaning of the poem that saw with using semantic analysis that focuses on analyzing lexical meaning, grammatical meaning, reference meaning, and analogical meaning. The research method that we used is a descriptive qualitative method. The result discussion showed that poem can be analyzed using semantic. This poem tells the love story.